PERJUANGAN TOKOH PEREMPUAN DALAM NOVEL AKU LUPA BAHWA AKU PEREMPUAN KARYA IHSAN ABDUL QUDDUS KAJIAN FEMINISME EKSISTENSIALIS - Natalia, Ade Lara; Rapi, Muhammad; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the struggle of the female character in the novel Aku Lupa Bahwa Aku Perempuan by Ihsan Abdul Quddus which is studied using existentialist feminist theory. This research uses descriptive qualitative research. The data source in this research is the novel entitled Aku Lupa Bahwa Aku Perempuan by Ihsan Abdul Quddus which was published by Alvabet in 2012 in Jakarta. The results of this research show that the female character Suad struggles to develop her career and demonstrate her existence. There are two strategies that women can use to achieve existence, including working women and intellectual women. Women can work, the female character Suad is serious about obtaining her rights in pursuing a career and success in terms of work and building relationships with many people to support the career she wants to achieve, and has a full sense of responsibility as a career woman. An intellectual woman, a Suad female figure who is successful, educated, a female leader and a Doctor